Parking Management in UTP Campus - Bakhtiar, Muhammad Izhar (IRC, 2015)
Every places needs a good parking management especially in the populated area. The number of people is getting higher throughout the year. Based on the statistics, the number of residents in the well-developed country is going to be increased drastically from 2015. People who are responsible needs to balance the demand and the supply of the parking. They are playing a very important role to overcome any problems regarding this matter. Without parking management, the parking problems will never be solved. This parking problem is not only causing frustrating and anxiety among the road users, it also influences them to cheat when it comes to park. This thing happened in most of the urban areas, even in the university campus, people would love to cheat by parking at the illegal places. There are so many parking abuses that can be found in the campus. It seems like the rules of parking in the campus are meaningless for them. That is why the main purpose of this project is to improve the parking management and reduce the parking problem in UTP campus. There are so many ways and solutions to solve the parking problem based on the research papers. Some of them are quiet suitable to be implemented in the university campus